The Analysis Of Central Character’s Ego-State In The Novel “The Pilgrimage” - Hanan, Ahmad; Sudirman, Sudirman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research was aimed to find out the central character’s ego-state in the novel “The Pilgrimage”. It focused on analyzing the central character’s ego-state in the novel “The Pilgrimage”. The method of this research was descriptive qualitative research. Data collection techniques that used are documentation, reading, re-read identification, note taking and classification. Data analysis techniques was used three step namely data reduction, data display, and conclusion drawing or verification. This research was analyzed by using psychology approaches of Eric Berne Transactional Analysis, especially concerning in Parent, Adult and Child system. The total of parent ego state found six, total of Adult ego state found nine, and total of child ego state found five.